2009
DOI: 10.1074/jbc.m807916200
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Intracellular Substrates and Products of Thimet Oligopeptidase in Human Embryonic Kidney 293 Cells

Abstract: Thimet oligopeptidase (EC 3.4.24.15; EP24.15) is an intracellular enzyme that has been proposed to metabolize peptides within cells, thereby affecting antigen presentation and G protein-coupled receptor signal transduction. However, only a small number of intracellular substrates of EP24.15 have been reported previously. Here we have identified over 100 peptides in human embryonic kidney 293 (HEK293) cells that are derived from intracellular proteins; many but not all of these peptides are substrates or produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
109
0
26

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 71 publications
(145 citation statements)
references
References 71 publications
10
109
0
26
Order By: Relevance
“…However, destruction of defined epitopes by TOP as studied by CTL recognition of target cells with suppressed expression of TOP, has thus far only been shown for the mouse H2-K b -presented SIINFEKL epitope from ovalbumin 5 . The role of TOP in the production of the PRA [190][191][192][193][194][195][196][197][198] and MART-1 epitopes is in accordance with a recent study that demonstrated that TOP in the cytosol both destroys and generates peptides of the length of class I ligands 40 . Thus the role of TOP in antigen processing appears to be twofold.…”
Section: Discussionsupporting
confidence: 59%
“…However, destruction of defined epitopes by TOP as studied by CTL recognition of target cells with suppressed expression of TOP, has thus far only been shown for the mouse H2-K b -presented SIINFEKL epitope from ovalbumin 5 . The role of TOP in the production of the PRA [190][191][192][193][194][195][196][197][198] and MART-1 epitopes is in accordance with a recent study that demonstrated that TOP in the cytosol both destroys and generates peptides of the length of class I ligands 40 . Thus the role of TOP in antigen processing appears to be twofold.…”
Section: Discussionsupporting
confidence: 59%
“…Although the intracellular peptides have not yet been shown to directly modulate protein-protein interactions in vivo, the in vitro use of surface plasmon resonance demonstrates that at concentrations of 1-50 M, several intracellular peptides can modulate the interactions of calmodulin and 14-3-3⑀ with proteins from the mouse brain cytoplasm or with recombinant EP24.15. One of these peptides (VFDVELL; VFD-7), shown to be a proteasome product (24), increases the free cytosolic Ca 2ϩ concentration in a dose-dependent manner but only if introduced into HEK293 cells (27).…”
mentioning
confidence: 99%
“…These peptides were used for affinity chromatography and were suggested to bind to a specific set of proteins, many involved in protein and vesicular traffic (23). In addition to the proteasome, thimet oligopeptidase (EC 3.4.24.15; EP24.15), which is an intracellular peptidase that only degrades small peptides (ϳ5-17 amino acids), was also shown to participate in intracellular peptide metabolism (24). By manipulating intracellular EP24.15 activity either by overexpressing the enzyme or inhibiting its activity by means of siRNA, it was possible to modulate G-protein-coupled receptor signal transduction in HEK293 and CHO-S cells (23,25).…”
mentioning
confidence: 99%
“…These three databases were composed of published studies [20,22,24,25,28,30,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] and a few additional studies that have not yet been published; these unpublished studies used identical methods, differing only in the treatment groups (which is not relevant to the present meta-analysis). The mouse database contains all peptidomic results from studies using mouse tissues-mainly brain regions, but also whole brain as well as heart, spleen, and testis.…”
Section: Methodsmentioning
confidence: 99%